Impact of implementing a pediatric early warning system on outcomes in hematopoietic stem cell transplant units in South America and Europe - Quijano-Lievano, Monica L.; Ramirez, Oscar; Chen, Yichen; Robles-Murguia, Maricela; Devidas, Meenakshi; Muñiz-Talavera, Hilmarie; Cárdenas-Aguirre, Adolfo; Portilla, Carlos; Castrillon, Diana; Rendon, Diana; De Paula, Andreia Ribeiro Pereira Aguiar; Diaz-Coronado, Rosdali; et al. (Frontiers in Oncology, 2025)
Background/AimEscala de Valoración de Alerta Temprana (EVAT) is a Spanish-language Pediatric Early Warning Score (PEWS) validated to predict the need for unplanned intensive care unit (ICU) transfer in hospitalized children with cancer. We assess the effect of PEWS implementation on hospitalized children undergoing hematopoietic stem cell transplantation (HSCT) in variable-resource centers in South America and Europe.MethodsWe analyzed data from a prospective registry of clinical deterioration events (CDE), defined as an unplanned ICU transfer, ICU-level intervention on the ward, ward cardiopulmonary arrest, or deterioration to death, among hospitals implementing PEWS. We included CDE occurring in patients under age 19 hospitalized in an HSCT unit between April 2017 and June 2024. We used the Wilcoxon rank sum test, chi-square test, and Fisher’s exact test to compare CDE occurring before PEWS implementation (pre-PEWS) and during/after PEWS implementation (post-PEWS).ResultsDuring the study period, we identified 221 CDE among 146 patients from six centers (South America n = 5; Europe n = 1). The median age was 9 years (IQR, 4–14), 68% (n = 150/220) were male, and 20% (n = 44/221) experienced more than one CDE. The overall event mortality rate was 18% (n = 39/221). Of 221 CDE, 71 occurred pre-PEWS implementation and 150 post-PEWS implementation. CDE post-PEWS were less likely due to respiratory distress (38%, n = 27/71 vs. 23% n = 35/150, p = 0.0348), had fewer organ systems with dysfunction at ICU transfer (median 2 [IQR 1–3] vs. 0 [IQR 0–2], p < 0.001), and had lower PIM2, which indicates a lower severity of illness at ICU transfer (median 5.0 [IQR 1.4–7.9] vs. 1.5 [IQR 1.2–3.4], p < 0.001). There was a non-significant decrease in clinical deterioration event mortality post-PEWS implementation (24%, n = 17/71 vs. 15%, n = 22/150, p = 0.1335).ConclusionsPEWS implementation promoted the early identification of critical illness as well as ICU transfer at a lower severity of illness for children undergoing HSCT. This work further supports the use of PEWS in the care of all children with cancer and blood disorders globally.